Konsep Pendidikan Karakter Perspektif Islam - Ubabuddin din Hafid (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
AbstractCharacter education is a value that must be learned, felt, and applied in the child's daily life. The concept of character education in Indonesia is the noble values education that is derived from Indonesian culture in the framework of guidance of young generation personality which includes three aspects, namely moral knowledge, moral attitude, and moral acting. The concept of Islamic education is the guidance given by someone to someone so that he develops maximally in accordance with Islamic teachings concerning the formation of body, mind, and the heart of the students. Keywords: Education, Character, Perspective Islam AbstrakPendidikan karakter merupakan sebuah nilai yang harus dipelajari, dirasakan, dan diterapkan dalam keseharian anak. Konsep pendidikan karakter di Indonesia adalah pendidikan nilai-nilai luhur yang bersumber dari budaya bangsa Indonesia dalam rangka pembinaan kepribadian generasi muda yang mencakup tiga aspek yaitu pengetahuan moral (moral knowing), sikap moral (moral feeling), dan perilaku moral (moral acting). Konsep pendidikan Islam adalah bimbingan yang diberikan oleh seseorang kepada seseorang agar ia berkembang secara maksimal sesuai dengan ajaran Islam yang menyangkut pembinaan jasmani, akal, dan hati anak didik. Kata Kunci: Pendidikan, Karakter, Perspektif Islam